lidR: An R package for analysis of Airborne Laser Scanning (ALS) data - Roussel, Jean-Romain; Auty, David; Coops, Nicholas C.; Tompalski, Piotr; Goodbody, Tristan R.H.; Meador, Andrew Sánchez; Bourdon, Jean-François; de Boissieu, Florian; Achim, Alexis (Remote sensing of environment, 2020)
Airborne laser scanning (ALS) is a remote sensing technology known for its applicability in natural resources management. By quantifying the three-dimensional structure of vegetation and underlying terrain using laser technology, ALS has been used extensively for enhancing geospatial knowledge in the fields of forestry and ecology. Structural descriptions of vegetation provide a means of estimating a range of ecologically pertinent attributes, such as height, volume, and above-ground biomass. The efficient processing of large, often technically complex datasets requires dedicated algorithms and software. The continued promise of ALS as a tool for improving ecological understanding is often dependent on user-created tools, methods, and approaches. Due to the proliferation of ALS among academic, governmental, and private-sector communities, paired with requirements to address a growing demand for open and accessible data, the ALS community is recognising the importance of free and open-source software (FOSS) and the importance of user-defined workflows. Herein, we describe the philosophy behind the development of the lidR package. Implemented in the R environment with a C/C++ backend, lidR is free, open-source and cross-platform software created to enable simple and creative processing workflows for forestry and ecology communities using ALS data. We review current algorithms used by the research community, and in doing so raise awareness of current successes and challenges associated with parameterisation and common implementation approaches. Through a detailed description of the package, we address the key considerations and the design philosophy that enables users to implement user-defined tools. We also discuss algorithm choices that make the package representative of the ‘state-of-the-art’ and we highlight some internal limitations through examples of processing time discrepancies. We conclude that the development of applications like lidR are of fundamental importance for developing transparent, flexible and open ALS tools to ensure not only reproducible workflows, but also to offer researchers the creative space required for the progress and development of the discipline. •We present the lidR package for ALS processing.•We document the design and aims of the package with an emphasis on its flexibility.•lidR assembles state-of-the-art algorithms from the literature.•lidR was conceived for users to implement transparent and reproducible workflows.•We provide evidence that liDR is increasingly being used for ALS-focused research.